Development of Critical Thinking Ability Through Sets Based Learning Approach: An Action Research on Grade XI IPA 1 SMAN 5 Dumai - Lamsihar P; Sapriya Sapriya; Kokom Komalasari (AIBPM Publisher, 2020)
The Development of students’critical thinking ability is crucial because based on the survey released by PISA (2018) found that the quality of Indonesian students’ critical thinking are in rank of 72 of 78 countries. One of the learning approaches to develop the critical thinking is through Science, Environment, Technology, and Society (SETS). This study was conducted in SMAN 5 Dumai, Riau in three cycles by using an action research consists of four phases: Plan, Action, Observation, and Reflection. While based on the students’ test result of Cycles 3, found that the scores of students’ critical thinking ability grade XI IPA 1 were 94 in which the lowest score was 76, the highest score was 100, and the level of learning success was 100 %.